Detector Leakage Gas Lpg Based On Telegram Notification Using Wemos D1 and Mq-6 Sensor - Uci Rahmalisa; Anita Febriani; Yuda Irawan (Journal of Robotics and Control (JRC), 2021)
Based on the test results of the National Standardization Agency (BSN), as much as 66% of the gas cylinders tested were found to be unfit for use was studied by zhang[1]. Along with the increasing use of LPG gas, the quality of gas cylinder products has decreased, and the need for supervision of gas cylinder products from the manufacturer, so it cannot cause danger was studied by dae[2]. Gas leaks most often come from the gap between the mouth of the tube and the regulator so that it can cause pollution to the polluted room. This is due to the seal that serves as a sealing gap between the gas cylinder valve and the regulator not working was studied by saeed[3]. This seal serves to close and isolate the gap between the regulator and the upper mouth of the gas cylinder so that gas leakage can be avoided, or it could also be caused by rat bites on the hose which can cause gas to leak. For this reason, a LPG gas leak detection device can be made remotely. Created a LPG gas leak detection system based on Wemos D1 microcontroller using telegram notification. The whole tool is divided into several parts which consist of mq-6 sensor, ESP8266-01S module, wemos d1 microcontroller, and buzzer. This tool works when the ESP8266-01S module searches for the nearest internet network and the mq-6 sensor detects lpg gas, from the ESP8266-01S module and mq-6 sensor then to the Wemos D1 microcontroller to process, from the Wemos D1 microcontroller then activates the buzzer as a warning alarm that then transfer data through the ESP8266-01S module to the website and give notification of a gas leak to the smartphone of the user of the device. The mq-6 sensor functions if the gas content value is above 80. The results show that the gas content value is more than 80 as detected lpg gas, because it has tested the system and when there is no lpg gas the gas content value is less than 80.